Environmental enrichment attenuates the age-related decline in the mRNA expression of steroidogenic enzymes and reduces the methylation state of the steroid 5α-reductase type 1 gene in the rat hippocampus - Rossetti, María Florencia (2015)
We analyzed the effects of aging and environmental enrichment on the mRNA expression and DNA methylation state of steroidogenic enzymes in the hippocampus. The effects of agingwere evaluated by comparing young adult (90-day-old) and middle-aged (450-day-old) female Wistar rats. To elucidate the effects of environmental enrichment, a subgroup of middle-aged rats exposed to sensory and social stimulation for 105 days was compared to rats housed under standard laboratory conditions. Aging decreased the transcription of neurosteroidogenic-related genes and increased the promoter methylation state of cytochrome P450 side chain cleavage, 3α-hydroxysteroid dehydrogenase (3α-HSD) and 5α-reductase-1. Exposure of middle-aged rats to environmental enrichment increased mRNA levels of 5α-reductase-1, 3α-HSD and cytochrome P450 17α-hydroxylase/c17,20-lyase and decreased the methylation state of the 5α-reductase-1 gene. Thus, sensory and social stimulation attenuate the age-related decline in the mRNA expression of hippocampal steroidogenic enzymes. Epigenetic mechanisms associated with differential promoter methylation could be involved.